Representation, memory, and development : essays in honor of Jean Mandler - Mandler, Jean Matter; Stein, Nancy L.; Bauer, Patricia J.; Rabinowitz, Mitchell (L. Erlbaum, 2002)
This work focuses on the child's development of memory, visual representation, and language. It should be useful for students and researchers in cognitive psychology, language acquisition, and memory.